Acción-estructura y génesis organizacional: la posición de emprendedores públicos en netdoms - Andrade Ribeiro, Antonio Carlos (El Colegio de México, 2022)
The paper analyzes the debate on Agency-Structure from rival approaches: sociological neoinstitutionalism and neostructural sociology. The first is discussed considering research on public entrepreneurship. The second takes White’s (2008) theory of netdoms as a reference. The objective is to identify characteris-tics of the social structure that enhance the performance of actors engaged in processes of organizational genesis. The analysis of the genesis of the Forums to Combat Corruption in Brazil illustrates the arguments presented. Techniques of analysis of social networks and factorials combine to typify identities and structural places that explain the role that concrete actors play in the dynamization of new institutions in the public sector. It is concluded that the organizational genesis demands competences distributed unevenly in the field.